2015
DOI: 10.1002/jnr.23559
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebroventricular oxytocin administration in rats enhances object recognition and increases expression of neurotrophins, microtubule‐associated protein 2, and synapsinI

Abstract: Brain oxytocin regulates a variety of social and affiliative behaviors and affects also learning and memory. However, mechanisms of its action at the level of neuronal circuits are not fully understood. The present study tests the hypothesis that molecular factors required for memory formation and synaptic plasticity, including brain-derived neurotrophic factor, neural growth factor, nestin, microtubule-associated protein 2 (MAP2), and synapsin I, are enhanced by central administration of oxytocin. We also inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 70 publications
1
45
0
Order By: Relevance
“…In contrast, in ovariectomized, steroid-treated female rats, 5 days of icv OXT (10 ng/hour) reduced anxiety levels and stress-induced c-Fos activation in relevant brain regions (66,72). In support of such sex differences, 7 days icv OXT (20 ng/hour) in male rats did not affect anxiety-related behavior (69).…”
Section: Chronic Effects Of Synthetic Oxt On Anxietymentioning
confidence: 79%
See 1 more Smart Citation
“…In contrast, in ovariectomized, steroid-treated female rats, 5 days of icv OXT (10 ng/hour) reduced anxiety levels and stress-induced c-Fos activation in relevant brain regions (66,72). In support of such sex differences, 7 days icv OXT (20 ng/hour) in male rats did not affect anxiety-related behavior (69).…”
Section: Chronic Effects Of Synthetic Oxt On Anxietymentioning
confidence: 79%
“…However, relevant basic studies are rare, and those performed reveal that chronic OXT effects strongly depend on the dose and duration of application, are likely to vary between male and female subjects (65)(66)(67)(68)(69)(70)(71)(72), and are dependent upon the innate level of anxiety (65). For example, in male mice, chronic icv infusion of OXT (10 ng/hour) over 2 weeks induced a robust increase in anxiety-related behavior in two independent behavioral tests, whereas a tenfold lower dose did not alter anxiety (67).…”
Section: Chronic Effects Of Synthetic Oxt On Anxietymentioning
confidence: 99%
“…Therefore, the potential procognitive effects of IRAP inhibitors may be mediated by increases in the levels and prolongation of activity of substrates including oxytocin. Oxytocin has recently been reported to enhance learning and memory, particularly in the novel recognition paradigm in rodents (Gard et al, 2012;Havranek et al, 2015). Although the effect of oxytocin on hippocampal dendritic spine density is not known, its effect on glucose uptake is documented.…”
Section: Macrocyclic Insulin-regulated Aminopeptidase Inhibitorsmentioning
confidence: 99%
“…The mPFC abundantly expresses oxytocin receptors (OT-R; Insel and Shapiro, 1992; Liu et al, 2005; Smeltzer et al, 2006; Nakajima et al, 2014; Mitre et al, 2016) and receives long range axonal projections from OT producing neurons in the hypothalamus (Sofroniew, 1983; Knobloch et al, 2012). In addition, OT has been shown to mediate the motherhood-induced enhancement in spatial memory (Tomizawa et al, 2003) and research in non-parous animals has shown that OT can influence various aspects of learning and memory (Gur et al, 2014; Havranek et al, 2015), including cognitive flexibility which is impaired in oxytocin receptor (OT-R) knockout mice (Sala et al, 2011; Chini et al, 2014). However, no previous work has investigated whether OT contributes to improved cognitive flexibility during the postpartum period.…”
Section: Introductionmentioning
confidence: 99%